Alternative organizing with social purpose: revisiting institutional analysis of market-based activity. (8th July 2019) - Mair, Johanna; Rathert, Nikolas
Abstract: Given rampant economic inequality, social exclusion and overconsumption, organizing in markets increasingly focuses on leveraging commercial activity for a social purpose. Alternative forms of organizing have developed to overcome the deficiencies of contemporary capitalism. They have become prevalent in numerous institutional contexts through types of organizations such as social enterprises, cooperatives and platform-based sharing economy organizations. Our objective is to ignite research on alternative organizing. We build on two important institutional perspectives, Neo-institutionalism and Comparative Capitalism, to investigate how these organizations diverge from the archetypal corporation. In addition, we develop a framework to guide institutional analysis of the origins, enabling conditions and consequences of alternative organizing in contemporary markets and society. We conclude by laying out pathways for future research.